A casa é deles?: reflexões sobre o cuidado em Serviços Residenciais Terapêuticos, a partir da perspectiva dos cuidadores - Muniz, Livia Prado (2023)
The dehospitalization of people who have experienced extended stays in psychiatric hospitals and the possibility of them residing in Therapeutic Residential Services are strategies outlined by the Brazilian Mental Health Policy. Legislation concerning these services does not specify caregiver qualifications for employment in these residences, and there is no consensus regarding the necessity of specific training for these professionals. This research aimed to identify the existing conceptions of care among caregivers in Therapeutic Residential Services and promote reflections on them, highlighting the formative processes of these professionals and their work practices. The study was carried out in Salto de Pirapora, a municipality in the metropolitan region of Sorocaba, known for its high number of Unified Health System beds in psychiatric hospitals. Beginning in 2012, the municipality initiated a deinstitutionalization process, resulting in the closure of two asylums. A qualitative approach was used in this research, which involved conducting a literature review on the topic, followed by exploratory interviews and questionnaire administration with 18 caregivers from Therapeutic Residential Services in the aforementioned municipality. Furthermore, non-directive interviews were conducted with 4 of them. Four conceptions of care were identified, which are mixed in the caregivers' speeches: Care in its professional dimension, Care as an act of charity, Care as the execution of domestic tasks, feminine and maternal care. It became evident that diversity in care practices within Therapeutic Residential Services is expressed in a contradictory way, through actions that sometimes help to promote autonomy, and at other times homogenize care. Thus, it is urgent to develop formative paths for these professionals so that residents can increasingly assume the house as their own and according to their strengths and needs, care for and be cared for. The Permanent Education strategy is a powerful way to face the various challenges related to the care practices discussed in this research. It is expected that the discussions proposed in this study will contribute to the appreciation and qualification of caregivers' work so that deinstitutionalization processes are sustained from anti-asylum references based on respect and freedom.